PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA PADA MATERI MEMBACA PEMAHAMAN UNTUK SISWA KELAS V SEKOLAH DASAR - R.R Ayu Dwi Maudi; Ni Made Ignityas Prima Astuti; Irwan Febryan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low reading comprehension skills of fifth-grade elementary school students, particularly in identifying the main idea, supporting details, and drawing conclusions from reading texts, as well as the limited use of interactive learning media in the learning process. This study aimed to: (1) develop an interactive learning media based on Canva for reading comprehension materials for fifth-grade students at SD Negeri 1 Tegal Badeng Barat; (2) determine the validity of the developed media based on the assessments of material and media experts; and (3) determine the practicality of the media based on the responses of teachers and students. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, questionnaires, and documentation. The research instruments included material expert validation sheets, media expert validation sheets, and practicality questionnaires for teachers and students. The data were analyzed using descriptive quantitative techniques through Gregory's content validity formula and the Criterion-Referenced Assessment (PAP) conversion. The results indicated that the Canva-based interactive learning media had a very high level of validity, with a Gregory content validity coefficient of 1.00. The media expert evaluation obtained an average score of 90.63%, while the material expert evaluation obtained an average score of 86.46%, both categorized as highly valid. Furthermore, the practicality test showed that the media was rated as highly practical by both teachers and students, indicating that it is easy to use, engaging, and suitable for implementation in fifth-grade reading comprehension learning.